Preparation Of Quality Financial Reports In Village Credit Institutions: A Study In Kukuh Customary Village - Sujana, Ni Made Wanda Diajeng; Kepramareni, Putu; Putra, I Putu Mega Juli Semara; Pradnyawati, KM Diah Monika (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study aims to enhance the competence of human resources in preparing high-quality financial reports at the Village Credit Institution (LPD) of Kukuh Traditional Village. As a microfinance institution, LPD plays a crucial role in the local economy, and good financial reporting is essential for implementing Good Corporate Governance (GCG) and increasing stakeholder trust. Method: The research was conducted through community service activities involving interviews, training, and evaluations. A pre-test and post-test approach was used to measure the effectiveness of the training. Practical Applications: The training provided practical knowledge and skills that are directly applicable to the daily financial reporting tasks of LPD staff, supporting the institutional goal of better governance and transparency. Conclusion: The evaluation showed a 64% increase in competence among the participants, indicating that the training program was effective and beneficial for improving human resource capacity at the LPD of Kukuh Traditional Village.